The Moderating Effect of Political Connections on the Relationship Between Corporate Social Responsibility and Tax Avoidance in the Energy Industry Sector - Novalina Arifianti; Heni Agustina; Ummu Imara Nusaibah; Elina Setyawati (Journal of World Science, 2026)
This study aims to determine the influence of CSR on tax avoidance and the moderating effect of political connections on the relationship between CSR and tax avoidance. The research was conducted on energy sector companies listed on the Indonesia Stock Exchange. The sample used comprised energy sector companies for the 2023–2024 period, totaling 66 observations. Data were collected through documentation techniques from annual reports and sustainability reports published on the Indonesia Stock Exchange website and company websites. The method used was Moderated Regression Analysis (MRA) with classical assumption tests, including normality, multicollinearity, autocorrelation, and heteroscedasticity tests. The results indicated that CSR has a significant positive effect on tax avoidance, suggesting that higher CSR disclosure is associated with lower tax avoidance practices. Political connections have a significant positive effect on tax avoidance, indicating that politically connected firms tend to engage in more aggressive tax strategies. Finally, political connections weaken the relationship between CSR and tax avoidance, demonstrating that political ties reduce the effectiveness of CSR in mitigating tax avoidance behavior. These findings contribute to the literature on corporate ethics, tax planning strategies, and the role of political economy in emerging markets